Effects of storage‐aged red blood cell transfusions on endothelial function in hospitalized patients. Issue 4 (13th November 2014) - Neuman, Robert; Hayek, Salim; Rahman, Ayaz; Poole, Joseph C.; Menon, Vivek; Sher, Salman; Newman, James L.; Karatela, Sulaiman; Polhemus, David; Lefer, David J.; De Staercke, Christine; Hooper, Craig; et al.
<x xml:space="preserve">Abstract</x> Background Clinical and animal studies indicate that transfusions of older stored red blood cells (RBCs) impair clinical outcomes as compared to fresh RBC transfusions. It has been suggested that this effect is due to inhibition of nitric oxide (NO)‐mediated vasodilation after transfusion of older RBC units. However, to date this effect has not been identified in human transfusion recipients. Study Design and Methods Forty‐three hospitalized patients with transfusion orders were randomly assigned to receive either fresh (<14 days) or older stored (>21 days) RBC units. Before transfusion, and at selected time points after the start of transfusion, endothelial function was assessed using noninvasive flow‐mediated dilation assays. Results After transfusion of older RBC units, there was a significant reduction in NO‐mediated vasodilation at 24 hours after transfusion (p = 0.045), while fresh RBC transfusions had no effect (p = 0.231). Conclusions This study suggests for the first time a significant inhibitory effect of transfused RBC units stored more than 21 days on NO‐mediated vasodilation in anemic hospitalized patients. This finding lends further support to the hypothesis that deranged NO signaling mediates adverse clinical effects of older RBC transfusions. Future investigations will be necessary to address possible confounding factors and confirm these results.